EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN MENGGUNAKAN METODE ROLE PLAYING UNTUK MEMINIMALISIR PERILAKU AGRESIF PADA PESERTA DIDIK DI SMK NEGERI 5 PADANG PADA KELAS X TITL 1 - Adit; Fitria Kasih; Rici kardo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the aggressive behavior exhibited by students of class X TITL 1 at SMK Negeri 5 Padang, both physically and verbally. This study aimed to determine the effectiveness of group guidance services using the role-playing method in minimizing students’ aggressive behavior. The study employed an experimental method with a One Group Pretest-Posttest design. The population consisted of 24 students, while the sample included 10 students selected using purposive sampling. Data were collected through questionnaires and analyzed using percentage analysis and a t-test. The results showed that before the intervention, students’ aggressive behavior was in the high category, with a percentage of 50%, while after the intervention, it decreased to the low category, with a percentage of 80%. The mean aggressive behavior score decreased from 170.6 in the pretest to 118.4 in the posttest. The t-test result showed a significance value of 0.000216 < 0.05, indicating that group guidance services using the role-playing method were effective in minimizing students’ aggressive behavior.